EFL TEACHERS’ TRANSLANGUAGING PEDAGOGY AND THE DEVELOPMENT OF BELIEFS ABOUT TRANSLANGUAGING - Kuandykov, Adam (Nazarbayev University Graduate School of Education, 2021)
The results of previous studies have shown that EFL teachers mainly held English-only beliefs in the context of Kazakhstan meaning that they preferred using the target language more than their learners’ mother tongue. Yet, with this belief, there is little room for translanguaging practices in EFL classrooms as the translanguaging pedagogy calls for the strategic inclusion of learners’ mother tongue into the lessons. However, these previous studies did not investigate the origins of teachers’ English-only beliefs in the context of Kazakhstan....
Keywords: type of access: open access